What makes a competent clinical teacher? - Wealthall, Stephen; Henning, Marcus (Canadian Medical Education Journal, 2012)
Background: Clinical teaching competency is a professional necessity ensuring that clinicians’ knowledge, skills and attitudes are effectively transmitted from experts to novices. The aim of this paper is to consider how clinical skills are transmitted from a historical and reflective perspective and to link these ideas with student and teacher perceptions of competence in clinical teaching. Methods: The reflections are informed by a Delphi process and professional development survey designed to capture students’ and clinicians’ ideas about the attributes of a competent clinical teacher. In addition, the survey process obtained information on the importance and ‘teachability’ of these characteristics. Results: Four key characteristics of the competent teacher emerged from the Delphi process: clinically competent, efficient organiser, group communicator and person–centred. In a subsequent survey, students were found to be more optimistic about the ‘teachability’ of these characteristics than clinicians and scored the attribute of person-centredness higher than clinicians. Clinicians, on the other hand, ascribed higher levels of importance to clinical competency, efficient organisation and group communication than students. Conclusions: The Delphi process created a non-threatening system for gathering student and clinician expectations of teachers and created a foundation for developing methods for evaluating clinical competency. This provided insights into differences between teachers’ and students’ expectations, their importance, and professional development.